2003
DOI: 10.1007/bf03020181
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine use is frequent in ambulatory surgery patients in Vancouver Canada

Abstract: P Pu ur rp po os se e: : To determine the incidence and nature of herbal medicine use among patients in a busy Canadian surgical day care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…Our CAM utility rates are higher than other reports of surgical populations, most of which have been conducted in North America. 2,5,7 The increase in use of CAM has significant implications for surgery.T he risk of herbal medication use and interaction with synthetic drugs is well reported (Table 7), as is the importance of detailed history taking and advice for discontinuation for certain products to prevent adverse reactions. [8][9][10] The true prevalence of interactions between herbal medications and allopathic drugs during anaesthesia and surgery is unknown.…”
Section: Table 4 Use Of Non-herbal Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our CAM utility rates are higher than other reports of surgical populations, most of which have been conducted in North America. 2,5,7 The increase in use of CAM has significant implications for surgery.T he risk of herbal medication use and interaction with synthetic drugs is well reported (Table 7), as is the importance of detailed history taking and advice for discontinuation for certain products to prevent adverse reactions. [8][9][10] The true prevalence of interactions between herbal medications and allopathic drugs during anaesthesia and surgery is unknown.…”
Section: Table 4 Use Of Non-herbal Therapiesmentioning
confidence: 99%
“…7 It is, therefore, essential that both patients and healthcare professionals have access to accurateand reliable information. In the US, this has already beenimplemented by launchingthe National Center for Complementary and Alternative Medicine (NCCAM).…”
Section: Herbal Onlymentioning
confidence: 99%
“…Seventy-four patients (46%) had informed their family physician that they were on herbal medicines, while 72 www.intechopen.com patients (44%) stated that their family physician was unaware that they were taking these medications. Of the 162 patients using herbal medicines, 54 were taking them on the advice of their doctor (33%) and 88 were self-prescribing (54%) (Lennox & Henderson, 2003). Women reported physician recommended (4.7%) at similar proportions as among males (Kelly et al, 2005).…”
Section: Recommendations Source For Herbal Medicine Usementioning
confidence: 91%
“…The largest numbers of consumers of herbal medicines (31.5% of users) were in the 31-45-yr-oldrange, which was also our largest group of patients. The46-60-yr-old group accounted for 25% of overall use and the over-60 group in our institution accounted for 17% (Lennox & Henderson, 2003). Research studied in surgery patients showed thirty-eight percent of the study population had consumed herbal medicine in the 2 years before surgery and 16% continued the use of herbal medicine in the month of surgery (Adusumilli et al, 2004).…”
Section: Frequency Of Herbal Medicine Usementioning
confidence: 99%
See 1 more Smart Citation